(untitled) (Economic and Political Thought, 2016)
The aim of the research undertaken in the article is to analyse one of the examples of sports diplomacy directed at rapprochement between two hostile states – the United States and Cuba. There have been a number of sports exchanges in baseball between the two states, which are the object of the research. The undertaken research is empirical. It is a case study concerning one of the examples of positive sports diplomacy. A decision-making method has been employed in order to analyse the data acquired from historical works, American documents and media coverage. As a results of the research it was determined that American-Cuban baseball diplomacy was only partially successful in bringing the two hostile states closer. Similarly, the choice of baseball as a tool of rapprochement had both positive and negative effects. It was also acknowledged that in fact baseball diplomacy between the USA and Cuba integrated both positive and negative elements of sports diplomacy.